Back Cover: Manganese‐Doping‐Induced Quantum Confinement within Host Perovskite Nanocrystals through Ruddlesden–Popper Defects (Angew. Chem. Int. Ed. 17/2020). Issue 17 (25th March 2020) - Paul, Sharmistha; Bladt, Eva; Richter, Alexander F.; Döblinger, Markus; Tong, Yu; Huang, He; Dey, Amrita; Bals, Sara; Debnath, Tushar; Polavarapu, Lakshminarayana; Feldmann, Jochen
Abstract : Mn 2+ doping into perovskite nanocrystals (NCs) leads to the formation of Ruddlesden–Popper (R.P.) defects and thus induces quantum confinement within the host NCs, as shown by T. Debnath, L. Polavarapu, and co‐workers in their Communication on page 6794 . At the R.P. defect planes, the octahedral layers of the interface are translated by exactly half a unit cell, and the carriers are confined to the individual domains separated by R.P. defect planes.